Optimization, characterization, and GC-MS analysis of recycled used engine oil by solvents and adsorbent extraction - Negasa Abdena Alemu; Ramesh Babu Nallamothu; Getachew Alemayehu Lakew (Scientific Reports)
Abstract Recycled engine oil was produced from used engine oil (15W-40) using a combination of MEK and 1-butanol solvents with an activated carbon adsorbent through the adsorption process. The experimental design matrix was prepared using Box-Behnken design (BBD) package within RSM, and recycled engine oil is optimized by response surface methodology (RSM). By varying solvent-to-oil ratio, the temperature and contact duration optimal conditions were identified as a 5.5:1 MEK and 1-butanol solvent-to-oil ratio, 50 min of contact, 42.5 °C, and constant 1 g of activated carbon adsorbent, yielding (65.20%, 65.20%) numerically and experimentally, respectively. Process factors (solvent-to-oil ratio, the temperature, and contact duration) influencing the yield of recycled engine oil are indicated by both contour and surface plots. The characterization of recycled oil indicates that its physiochemical properties, such as density, viscosity, flash point, pour point, and total base number, met the ASTM standards. GC–MS analysis further identified the presence of natural base oil, additives (polymeric, metallic, and non-metallic), and oxidation compounds, indicating the efficacy of the recycling process in recovering valuable components from the used engine oil. Before and after adsorption, FTIR is used to analysis the effect of optimized engine oil adsorption on the activated carbon adsorbent. The recycling method that has been optimized indicates potential for sustainable resource consumption and conservation, which may help the vehicle industry practice environmental stewardship.